ZHU DANDAN (A): PROMOTIONS and TEACHING NOTE - Ma, S.; Trigo, V. (IVEY CASE CENTER, 2013)
The generation born in China in the 1980s has become an important force in the country's labour market. Members of this generation were the first to grow up in a market economy with daily access to the Internet, and are considered to have different work values than past generations. Also, most were born and raised in single-child families and generally demonstrate more individualistic behaviours and less willingness to follow the norms of previous generations. This case describes the promotion story of Zhu Dandan, a member of the 1980s generation, and illustrates the different work values, behaviours and management style of her generation, as well as the challenges of managing it.